RISING PROFILE OF ORAL CAVITY PROTOZOA AMONGST DENTAL PATIENTS IN SOUTH EASTERN NIGERIA - Ani, Ogonna Christiana; Agbo, Emmanuel E; Nnamonu, Emmanuel Ikechukwu; Onyeidu, Samuel Osemedua; Onyeidu, Blessing Uchechukwu; Okwerekwu, Nkiru Joy (LIFE: International Journal of Health and Life-Sciences, 2020)
The observed low knowledge of oral hygiene and the need to investigate the possible cause(s) of the existing oral diseases in our study area motivated this study. This study investigated the prevalence of human oral protozoan parasites amongst dental patients attending the clinic at Federal Teaching Hospital Abakaliki, South Eastern Nigeria. A total of 180 patients (72 males and 108 females) were sampled. Dental plaque, dental calculus, and saliva samples were collected from the patients. Samples were analyzed following standard methods. An overall prevalence rate of 40% occurred. Entamoeba gingivalis was the most encountered 28 (15.56%), followed by Trichomonas tenax 24 (13.33%) while mixed infections were recorded in 20 (11.11%) patients. The prevalence of both protozoans was higher in females 44 (40.74%) than in males 28 (38.89%). The highest prevalence was recorded among patients within the age range of ≤ 50 years (22 (81.48 %)) and least within the age range of ≤ 20 years 4(16.00%). There was an observed significant relationship between age and oral hygiene status. We, therefore report that poor oral hygiene is a predisposing factor that exposes the buccal cavity to frequent colonization by parasites. Constant oral health education should be encouraged especially among dental patients.